2017
DOI: 10.1039/c7ob00378a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of oxazolidinones: rhodium-catalyzed C–H amination of N-mesyloxycarbamates

Abstract: N-Mesyloxycarbamates undergo intramolecular C-H amination reactions to afford oxazolidinones in good to excellent yields in the presence of rhodium(ii) carboxylate catalysts. The reaction is performed under green conditions and potassium carbonate is used, forming biodegradable potassium mesylate as a reaction by-product. This method enables the production of electron-rich, electron-deficient, aromatic and heteroaromatic oxazolidinones in good to excellent yields. Conformationally restricted cyclic secondary N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 86 publications
0
8
0
Order By: Relevance
“…This result led us to envision to develop alternative types of triplet acceptors to enable the desired cyclization. In fact, there are several precedents showing the activation of hydroxamates via photoredox catalysis to generate amidyl radicals. In addition, hydroxamates were used as a metal nitrenoid precursor by the action of transition metal catalysts. , …”
Section: Resultsmentioning
confidence: 99%
“…This result led us to envision to develop alternative types of triplet acceptors to enable the desired cyclization. In fact, there are several precedents showing the activation of hydroxamates via photoredox catalysis to generate amidyl radicals. In addition, hydroxamates were used as a metal nitrenoid precursor by the action of transition metal catalysts. , …”
Section: Resultsmentioning
confidence: 99%
“…Experimentally, the reaction between N -mesyloxycarbamate A and potassium acetate or sodium 2-ethylhexanoate (known to be soluble in organic solvents) produced the potassium or sodium N -mesyloxycarbamate salt as a white precipitate (Scheme 3). 12 The rhodium catalyst was not necessary for salt generation to occur. When the deprotonation with potassium acetate was studied in silico , all three models afforded potassium N -mesyloxycarbamate salts ( Salt-K ) with a small energy barrier of 0.5 to 4.0 kcal mol –1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Significant advantages are associated with metal-catalyzed C–H amination via nitrene insertion, including mild reaction conditions as well as high chemo- and stereoselectivities 5,6. Among these processes, intramolecular metal-catalyzed C–H aminations with carbamate derivatives afford oxazolidinones in good to excellent yields,712 whereas intermolecular reactions produce amines bearing readily removable carbamate protecting groups (Scheme 1). 1316 Very recently, the synthesis of γ-lactams via C–H amidation was reported using tailored iridium catalysts 17.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, In 2017, Lebel and colleagues introduced convergent rhodium(II)‐catalyzed intramolecular C−H amination of N ‐mesyloxycarbamate 64 for the synthesis of oxazolidinones 65 using ethyl acetate or methanol as a solvent (Scheme 17). [32] Several palpable merits of this strategy are simple operation, easily removable biodegradable low molecular weight byproducts, and insensitivity for humidity. The results showed that the use of 3 mol% of rhodium(II) triphenylacetate dimer complex Rh 2 (tpa) 4 as the catalyst was the best choice.…”
Section: Synthesis Of 2‐oxazolidinonesmentioning
confidence: 99%